Intellectual capital and productivity of Malaysian general insurers - Chen F.-C.; Liu Z.-J.; Kweh Q.L. (2023)
This study investigates changes in productivity of general insurance firms in Malaysia for the period from 2008 to 2011. Moreover, this study examines the impact of intellectual capital on changes in productivity. In the first stage, this study applies the Malmquist productivity index (MPI) of data envelopment analysis (DEA) and the MPI with bootstrapping approach to evaluate changes in productivity. In the second stage, this study examines the impact of intellectual capital on changes in productivity through OLS and Tobit regressions. Our MPI findings indicate that all but one sample firms experienced growth in productivity over the sample period. Moreover, the use of the MPI with bootstrapping approach provides an effective analysis of MPI estimates. Our regression analysis reveals that VAIC™ and its individual components have significantly positive impacts on changes in productivity. We suggest that general insurers in Malaysia should invest in intellectual capital, including to improve their managerial skills, to gain sustainable growth in productivity. Our findings corroborate the initiative carried out by the Malaysian government, which continuously emphasize the importance of IC. The findings of this study may lead to a better understanding of the relative changes in total productivity of general insurance firms. By identifying changes in efficiency and changes in technology, better management decisions can be made to achieve greater productivity. Moreover, through the bootstrap estimation, we are able to determine whether estimated increases or decreases are statistically significant. © 2013 .